Caracterização funcional do fator da tradução eIF5A por meio de interações genéticas - Galvão, Fábio Carrilho [UNESP] (2015)
The translation factor 5A (eIF5A) is highly conserved in arqueas and eukaryotes and essential for cell viability. eIF5A is the only protein known to contain the essential amino acid hypusine, generated by a post-translational modification known as hypusination which occurs in two enzymatic steps catalyzed by the enzymes deoxyhypusine synthase (DYS1) and deoxyhypusine hydroxylase (Lia1) enzymes. Although eIF5A has been implicated with the elongation step of translation, its specific function and the role of the hypusine residue is still unknown. For this purpose, this work further characterized the dys1-1 mutant, a conditional mutant of the deoxyhypusine synthase. The results revealed that the dys1-1 mutant shows a polysome profile defect characteristic of translation elongation factors, decrease of eIF5A binding to the polysome fractions and reduction of the total protein synthesis rate. Furthemore, genetic interaction analyses of eIF5A driven by hypotheses, from published and previous data obtained in our laboratory, were performed and revealed synthetic lethality between ASC1 mutants and the dys1-1 mutant and negative genetic interactions (synthetic sick) between the tif51A-1 mutant and mutants of genes related with secretion, specifically those involved with the co-translational translocation of proteins into the endoplasmic reticulum. Finally, high throuput genetic interaction analyses by Synthetic Genetic Array (SGA) were carried out using different eIF5A mutants and two S. cerevisiae mutant strain collections (deletion strains and temperature-sensitive mutants). The results showed, respectively, 338 and 239 genes of the deletion mutant and the temperature-sensitive mutant collections interacting with eIF5A mutants. A total of 577 positive and negative genetic interactions were observed. Moreover, the gene ontology analysis revealed genes involved with cell cycle (53%), DNA repair (18%), translation (16%) and vesicular trafficking/...